Faces of cellular senescence in skin aging. (September 2021) - Ho, Chin Yee; Dreesen, Oliver
Highlights: Senescent cells accumulate in the aging skin due to intrinsic and extrinsic factors. Senescent cells may alter communication between skin layers and perturb skin homeostasis. Mitochondria and autophagy play key roles in skin homeostasis and aging. Accumulation of DNA damage is a driver of skin cell senescence and possibly differentiation. Terminally differentiated and senescent cells may respond differently to DNA damage. Abstract: The skin is comprised of different cell types with different proliferative capacities. Skin aging occurs with chronological age and upon exposure to extrinsic factors such as photodamage. During aging, senescent cells accumulate in different compartments of the human skin, leading to impaired skin physiology. Diverse skin cell types may respond differently to senescence-inducing stimuli and it is not clear how this results in aging-associated skin phenotypes and pathologies. This review aims to examine and provide an overview of current evidence of cellular senescence in the skin. We will focus on cellular characteristics and behaviour of different skin cell types undergoing senescence in the epidermis and dermis, with a particular focus on the complex interplay between mitochondrial dysfunction, autophagy and DNA damage pathways. We will also examine how the dermis and epidermis cope with the accumulation of DNA damage during aging.